Heavy Metals Contamination Assessment Using Pollution Indices for Spring Water in Barwari Bala Villages, Duhok, Kurdistan Region-Iraq - Mohammed Jalil Qasim; Hajar Ameen Ameen; Azzedin Ali Marouf (Environment and Natural Resources Journal, 2025)
Regular quality monitoring of drinking water resources is crucial for ensuring a safe drinking water supply for various users. Thus, this study was carried out to assess water safety for human drinking in terms of heavy metal content using pollution indices for spring water in Barwari Bala Villages located in Duhok City, Kurdistan Region of Iraq. Six spring water samples were collected at 10 to 15 day intervals from 10 areas during the summer of 2023. All 60 samples were analyzed in the laboratory to evaluate heavy metal concentrations, including manganese (Mn), chromium (Cr), iron (Fe), zinc (Zn), copper (Cu), cadmium (Cd), and lead (Pb). The overall quality of water was then assessed by utilizing pollution indices, including the degree of contamination (Cd), the heavy metal evaluation index (HEI), and the heavy metal pollution index (HPI). The results revealed that the concentrations of all the selected heavy metals found in spring water samples were lower than the permissible limits based on Iraqi standards, except for Pb in sites SW1 (Kyle Baze), SW2 (Kani Mazne), and SW8 (Derishke), which had higher concentrations of Pb depending on the prescribed limits (10 µg/L). According to metal pollution indices, the values of all the indices were lower than their critical ranges of contamination, indicating that the water of every site was safe for drinking. However, greater concentrations of Pb in spring water at sites SW1, SW2, and SW8 might have an adverse impact on human consumption in the long term. Thus, the treatment of spring water at these sites before utilization is highly recommended to ensure safe water for consumption. Further research is needed to determine the causes and contributing factors behind the rising lead (Pb) levels observed at those locations, as well as to develop appropriate treatment strategies to mitigate contamination.